Entrepreneurship education - Jones, Paul 1967-; Pittaway, Luke (Contemporary issues in entrepreneurship research)
Prelims -- New perspectives on entrepreneurship education -- Studies of the impact of entrepreneurship education upon student communities -- Novel entrepreneurship education pedagogy -- Entrepreneurship education intervention -- About the Editors -- About the Authors -- Index